A definition and model for sustainability in major sports events - Shreyya Rajagopal; Léonie Brodmann; Martin Müller; David Gogishvili; Markus Lang; Lucie Schoch; Ioannis Konstantopoulos; Stefano Caneppele (Current Issues in Sport Science)
Sustainability has become a key concern of major sports events. Yet, the field lacks both a consistent definition and a conceptual model for sustainable major events. This hampers the emergence of a shared theoretical understanding of sustainability as an epistemic object and the building of a practical framework to guide the sector towards greater sustainability. This paper mobilises a three-wave Delphi study with 55 experts to construct a definition of a sustainable major sports event. Through the three Delphi waves, the paper specifies a concentric ‘discus model’ of sustainability with three spheres: environmental factors as a limiting condition on the outside, economics and governance as the foundation at the centre, and social wellbeing as the key goal in the middle. It identifies 18 dimensions (six in each sphere) to serve as a further operationalisation of the conceptual model into a future framework. The paper maps these 18 dimensions on the UN Sustainable Development Goals and suggests that the discus model can serve as a basis for sports events to formulate a research-based sustainability strategy.